Exploring the perceived benefits and risk of electroconvulsive therapy in treating bipolar disorder: a qualitative study on anaesthesiologists, psychologists and psychiatrists, using interviews - Mabuza, Nolizwe Carol (The IIE, 2020)
Electroconvulsive therapy (ECT) is often portrayed as crude and barbaric as much of the perceptions have been from the results of early treatments in which a high dosage of electricity were administered without anaesthesia leading to memory loss, physical harm, catatonia and other fatalities (Wiley, 2017). Currently understanding the risk/reward ratio of this treatment is unclear as scholars like Devanand, Fitzsimons, Prudic, and Sackeim (1995) only focused on the risks of western studies. This study consisted of 6 medical professionals in South Africa with the aim to explore what they think the risks and rewards of using ECT are in terms of treating bipolar disorders in a South African context. Non-probability sampling methods, in-depth interviews and qualitative content analysis were used to gather data and results showed ECT is portrayed as an invasive treatment that is not sensitive to all pathologies. Currently the risk and rewards of using this form of treatment to treat bipolar disorders is equivalent as they depend on the severity of symptoms, physiology of the patient and the severity of their conditions. Clinicians believe that more research should be conducted in order to find more natural ways of stimulating neurotransmitters by using technologies and drugs that can encapsulate hormones that target receptors.
Keywords: Electroconvulsive therapy (ECT); Bipolar disorder; Anaesthesiologists; Psychologists; Psychiatrists; Perceived benefits